Book Review on Vaidyamanorama - Viji , P C; Subin , V R; Jigeesh , P P (International Research Journal of Ayurveda & Yoga, 2022)
An old Malayalam treatise, called Vaidyamanorama contains recipes for treating various illnesses. It also goes by the name Chikitsakrama. There are two more works with the title "Vaidyamanorama," one of which is thought to have been authored by Kalidasa (the probable period between AD 1000 - 1500) and the other, "Chikitsakrama," is quite similar to this one. The other two, in explanation of formulations in detail for each disease as well. The author of this treatise and the period in which this was written are unknown. However on the verification of the available manuscripts or records points to the possibility that, it was originally written by one of the members of the Ashtavaidya tradition. This book is published on the basis of 2 incomplete manuscripts procured from families in Kerala having rich Ayurveda Legacy. Vaidyamanorama was first published by Vayaskara N. S. Mooss in two editions for the magazine Vaidyasaradhi in 1944 and 1947. Cheppaad Achyutavarier, a proponent of Sanskrit language, Grammar, Astrology, and Tarka, contributed the annotations. The currently available book is the 3rd edition, published in August 2020, by the Unni Mooss foundation. It consists of 434 pages with MRP of Rs.500/- The book here focuses, the present day Vaidyamanorama is different